Ironing out the way for green steel financing a green hydrogen-based: Ironmaking plant in an emerging market - Hasan Muslemani; Stephen Craen; Paul Butterworth; Daniel Duma; Martin Lambert (The Oxford Institute for Energy Studies, 2024)
The iron/steel industry is one of the highest emitting sectors, contributing 7-9% of overall global emissions. As population and economic growth will demand more steel as a key building block of society, the need to decarbonize the sector is critical. This paper assesses the financing requirements and feasibility of an archetype green hydrogen-based ironmaking project in a developing country, for export of green iron into developed countries where steel can then be produced. This work assesses technical and market challenges which may face such a project and suggest potential solutions, including in relation to the supply of clean electricity and raw materials to market exposure and the possibility of absorbing the green premium. The authors also discuss possible project commercial structures, including key agreements which will be needed in place to make the project financeable, along with debt and equity requirements of the project.
Keywords: 330; carbon management; green hydrogen; Green steel; Hydrogen; industrial decarbonisation; iron; steel